UTILIZATION OF MACHINE TECHNOLOGY IN INCREASING INSTANT GRINGER PRODUCTION - Asnawi; Ronald Fransyaigu; Hanafiah; Ary Kiswanto Kenedi; Suheri (Global Science Society, 2021)
The ginger industry in East Aceh district is widely developed through home industries which are an important part of small and medium industries. This industry is mostly done by housewives on the sidelines of their busy household. The "Halia Instans" industry is one of the small businesses that develops processed ginger products. The raw materials for Instant Ginger will be processed through the following production process, first the ginger is washed clean or the soil is gone, then drained for a few seconds, then the ginger is blended, then after blending the finely ground ginger is squeezed using a machine and processed or cooked with an existing recipe so that produce ginger extract.. the results of the implementation of activities Encourage partners to cooperate with related parties in order to increase the production and marketing of Instant Ginger and add facilities to help increase ginger commodities in the overseas safe area